Prevention of Febrile Neutropenia in Acute leukemia Patients: Role of Nurse - Worapanwisit, Titaporn; Paritsiraprapa, Chompoo; Rotchanarak, Witchaya (Journal of The Royal Thai Army Nurses, 2020)
Acute leukemia is a disease caused by abnormalities of blood stem cells in the bone marrow. The chemotherapy is important drug which was used to destroy leukemic cells in acute leukemia patients. Febrile neutropenia is a serious complication of chemotherapy that is a major cause of death. S-SHIP-BE technique was used to prevention infection from febrile neutropenia. It comprised of screening, staff educating, hand hygiene washing, zoning, personal protective equipment wearing, bathing, and environment managing. These are important roles of nurse to promote the quality of life and they were effective techniques to reduce death rate in acute leukemia patients.